The impact of teamwork on an organization’s performance: a cooperative game’s approach - Askari, G.; Asghri, N.; Gordji, M. E.; Asgari, H.; Filipe, J. A.; Azar, A. (Mathematics, 2020)
In this article we study the impact of teamwork on the organizations’ performance, considering a cooperative game’s framework. To promote the teamwork culture, performance indexes are considered individually and collectively, respectively, and by comparing the scores that every employee earns individually and collectively, their differences become obvious. In this approach, a cooperative games’ model is used in order to improve the organization’s performance. The proposed model, in addition to evaluating the organization and employee's activities, can implement all payments, including the overtime pay, reward, etc., fairly and along with increasing performance and satisfaction. The cooperative approach creates effective communications between employees and authorities and enhances their motivation for teamwork. Moreover, results can be used for decisions related to employees (such as promotion, transition, firing, and detachment), analysis of training requirements, employees’ development, and research and plan valuation. Our findings show that the collaborative coefficient is a key factor in increasing productivity and improving the efficiency of an organization in the long run. The collaborative coefficient is a new concept in teamwork that has rarely been considered in scientific research.